Analisis Efisiensi Gas Turbine Unit 2 Sebelum dan Sesudah Overhaul di PLTGU Tanjung Uncang - Purba, Jhon Hericson; Yuwana, Farraz Akbar (Jurnal Teknologi dan Riset Terapan (JATRA), 2024)
An overhaul was conducted for maintenance on Gas Turbine unit 2, type SGT 800 at PLTGU Tanjung Uncang, with the purpose of preventive maintenance. The operating hours of the gas turbine exceeded the maintenance schedule, reaching around 36,000 working hours, whereas maintenance should have occurred between 20,000 to 30,000 working hours. The discrepancy between the actual working hours and the standard maintenance schedule for the gas turbine was due to the Tanjung Uncang power plant operating on a base load system, requiring the turbine to run continuously for 24 hours. This study aims to analyze the thermal efficiency, heat rate, and specific fuel consumption before and after the overhaul. The method used in this study is the thermodynamic analysis calculation of the Brayton cycle. By performing thermodynamic analysis to determine the gas turbine's efficiency and calculating specific fuel consumption, heat rate, and thermal efficiency under load, the comparison of the gas turbine's efficiency values can be determined. The thermal efficiency after the overhaul increased by 5.17%. The heat rate after the overhaul decreased by 1867.806 kJ/kWh. The specific fuel consumption after the overhaul decreased by 0.037 kg/kWh. The overhaul impacted the maximum load that could be produced by gas turbine unit 2. Before the overhaul, the maximum load was 36 MW. After the overhaul, the maximum load increased to 45 MW. This increase in load is influenced by temperature, fuel flow rate, and pressure.